2016
DOI: 10.1109/tpwrs.2015.2407363
|View full text |Cite
|
Sign up to set email alerts
|

AC-Feasibility on Tree Networks is NP-Hard

Abstract: Recent years have witnessed significant interest in convex relaxations of the power flows, with several papers showing that the second-order cone relaxation is tight for tree networks under various conditions on loads or voltages. This paper shows that ac-feasibility, i.e., to find whether some generator dispatch can satisfy a given demand, is NP-hard for tree networks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
129
1

Year Published

2017
2017
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(135 citation statements)
references
References 10 publications
0
129
1
Order By: Relevance
“…Because there are additional relaxations we have introduced in (3a)-(4b), the final solutions of the proposed SOC-ACOPF model are generally not tight for the constraint (1g) in ACOPF. Using interior point method to solve the proposed SOC-ACOPF model in polynomial time does not violate the NP-hardness proof [34], [35] of ACOPF because the proposed SOC-ACOPF is still a relaxed model of ACOPF. …”
Section: Theoremmentioning
confidence: 99%
“…Because there are additional relaxations we have introduced in (3a)-(4b), the final solutions of the proposed SOC-ACOPF model are generally not tight for the constraint (1g) in ACOPF. Using interior point method to solve the proposed SOC-ACOPF model in polynomial time does not violate the NP-hardness proof [34], [35] of ACOPF because the proposed SOC-ACOPF is still a relaxed model of ACOPF. …”
Section: Theoremmentioning
confidence: 99%
“…Lehmann et al showed that the DC power analogue of s ‐ t ‐FlowFeasibility is strongly NP‐hard for planar graphs of maximum degree 3. They also show that a generalization of s ‐ t ‐MaxFlow with at least two sources and sinks cannot be approximated in polynomial time better than 2logn1ϵ for an ϵ > 0 unless the problems in NP can be solved in quasi‐polynomial deterministic time.…”
Section: Basic Modelmentioning
confidence: 99%
“…The SDP relaxation was exact (or proved infeasibility) 2 To obtain satisfactory convergence of the SDP solver, these systems are pre-processed to remove low-impedance lines (i.e., lines whose impedance values have magnitudes less than 1 × 10 −3 per unit) as in [15]. 3 These relaxation gaps are calculated using the objective values from the SDP relaxation (9) and solutions obtained either from the second-order moment relaxation [14] (where possible) or from MATPOWER [24]. 4 Even the minor modifications performed when pre-processing lowimpedance lines and enforcing minimum line resistances are not needed for some test cases.…”
Section: A Generation Cost Constraintmentioning
confidence: 99%
“…The OPF problem is non-convex due to the non-linear power flow equations, may have local optima [1], and is generally NP-Hard [2], even for relatively simple cases such as treetopologies [3]. There is a large literature on solving OPF problems using local optimization techniques (e.g., successive quadratic programs, Lagrangian relaxation, heuristic optimization, and interior point methods [4], [5]).…”
Section: Introductionmentioning
confidence: 99%